Playing games with 'good farming': exploring the potential impact of disease control policies on farmers' cattle purchasing practices. (May 2022) - Enticott, Gareth; Little, Ruth
Abstract: This paper explores how understandings of what constitutes 'good farming' play a significant role in shaping farmers' cattle purchasing decisions. The purchasing of cattle has been shown to be one of the most significant biosecurity risks resulting in disease transmission and translocation. As a result, biosecurity policy makers have sought to develop behavioural interventions to reduce disease risks associated with cattle purchasing. In other policy areas, notions of 'good farming' have been shown to influence farmers' decision-making, and reflect the role of heuristics and social norms in behavioural theory. A scenario-based cattle purchasing game was developed to compare the potential impact of different ways of measuring and visualising 'good farming' to reduce the spread of animal disease (specifically bovine Tuberculosis). Qualitative and quantitative analysis of farmers' purchasing rationales given during the game suggested that cattle purchasing is shaped by a strategy of 'fitting the system' in which cattle are primarily selected on the basis of being able to fit existing farming systems. Symbols of good farming pictured in cattle sales adverts – such as good stockmanship, and cleanliness – were important elements of this strategy. Attempts to quantify aspects of good farming were welcomed but not fully trusted. Good farming status was nevertheless more important than financial incentives when deciding which cattle to purchase. In conclusion, the paper highlights the relevance of these findings for biosecurity policy makers seeking to use behavioural insights to manage animal disease. Highlights: Cattle purchasing is a significant risk factors in disease transmission. Changing farmers' cattle purchasing behaviours could enhance disease control. A scenario-based game was created to analyse farmers' purchasing decisions. Information on disease and financial compensation have limited influence on decisions. Farmer perceptions of 'good farming' are important in shaping cattle purchasing decisions.